2006
DOI: 10.1375/twin.9.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Rates Among Singletons, Twins and Triplets in Japan: A Population-Based Study

Abstract: This study was performed to determine the rates of breastfeeding among singletons, twins and triplets in Japan, and identify factors associated with the decision to breastfeed or bottle-feed. We analyzed a database of medical check-up of infants aged 3 to 6 months between April 2001 and July 2004 in Nishinomiya City in Japan. This medical check-up is given to almost 100% of infants in Japan and the data of 15,262 infants were analyzed. Among these, 14,963 (98.0%) were singletons, 290 (1.9%) were twins and 9 (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 20 publications
6
13
0
1
Order By: Relevance
“…Similar to our findings, previous studies suggested a dose–response relationship between parity, and breastfeeding initiation and exclusivity among mothers of both singleton and twin infants [23,26,36,74,83]. Another study found that first-born children were more likely to be weaned early and introduced to cow’s milk and formula early [84].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, previous studies suggested a dose–response relationship between parity, and breastfeeding initiation and exclusivity among mothers of both singleton and twin infants [23,26,36,74,83]. Another study found that first-born children were more likely to be weaned early and introduced to cow’s milk and formula early [84].…”
Section: Discussionsupporting
confidence: 91%
“…However, a weakness of our study was that the only information we had was breastfeeding at discharge from the neonatal unit without any information on the duration of breastfeeding. Consistent with previous studies, 54 our findings showed that breastfeeding was signifi- cantly less frequent in twins (17.3%) than in singletons (24.7%) (P=.002). It is also likely that the duration of breastfeeding was shorter for multiple births.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…A population based study of 15,262 infants confirmed that the mean age of mothers who chose formula feeding was significantly younger than those who chose ‘full’ and ‘Any Breastfeeding’ (p < 0.001) [21]. This study was cross-sectional and analysed a database of infants aged three to six months attending for medical examinations, which has a very high response rate in Japan.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, a study using data from the National Survey of 46,569 infants showed that mothers in their 30s and 40s were less likely to continue Exclusive Breastfeeding at six months postpartum than mothers in their 20s (aOR = 0.89, 95% CI = 0.84-0.94 for their 30s; aOR = 0.56, 95% CI = 0.48-0.65 for their 40s, respectively) [20]. The National Survey used a cross-sectional study design and found different results to the study by Yokoyama et al [21]. Moreover, Sasaki et al found no correlation between maternal age and Exclusive Breastfeeding at four months postpartum in a longitudinal study (p = 0.93, n = 908) [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation